Ionic conductivity studies of 49% poly(methyl methacrylate)-grafted natural rubber-based solid polymer electrolytes - Su'ait M.S.; Ahmad A.; Rahman M.Y.A. (2023)
The potential of 49% poly(methyl methacrylate)-grafted natural rubber (MG49) as a solid polymer electrolyte film in rechargeable batteries system were explored. The flat, thin, and flexible films were prepared by solution casting technique. The ionic conductivity was investigated by alternating current impedance spectroscopy. The highest conductivity of 2.3 10-7 Scm-1 was obtained at 20wt.% of LiBF4 salts content, while 4.0 10-8 Scm-1 was obtained at 15wt.% LiClO4 salts loading. The observation on structure performed by X-ray diffraction shows the highest conductivity appears at amorphous phase. Springer-Verlag 2008.